(Cr0.2Mn0.2Fe0.2Co0.2Mo0.2)B: A novel high-entropy monoboride with good electromagnetic interference shielding performance in K-band. (30th June 2021) - Zhang, Haiming; Zhao, Biao; Dai, Fu-Zhi; Xiang, Huimin; Zhang, Zhili; Zhou, Yanchun
Graphical abstract: Highlights: A novel high-entropy (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B was designed and prepared in both powder and bulk form for the first time. Although MnB, FeB, CoB, CrB and MoB have different crystal structures, HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B exhibits MnB type structure. The lattice parameters, microstructure, electrical conductivity and Vickers hardness of HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B were determined. HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B shows good EMI shielding performance, which is promising as a novel EMI shielding material. Abstract: A novel equimolar high-entropy (HE) transition metal monoboride, (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B, was designed and prepared in powder and bulk form by high temperature elemental reaction method and spark plasma sintering (SPS) method, respectively. XRD analysis shows that HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B possesses orthorhombic structure with Pnma space group. Through Rietveld refinement, the lattice parameters of HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B are a = 5.6675, b = 2.9714, c = 4.2209 and the theoretical density is 6.95 g/cm 3 . The Vickers hardness and electrical conductivity of HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B bulk with relative density of 90 % is 12.3 ± 0.5 GPa and 0.49 ± 0.04 × 10 6 S/m, respectively. Due to high electrical conductivity, HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B bulk with 3.0 mm thickness displays superior EMI shielding performance in 18.0–26.5 GHz (K-band), and the average values of SET, SER, and SEA are 23.3 dB, 13.9 dB, and 9.4 dB, respectively. The EMI shielding mechanism of HE (Cr0.2 Mn0.2 Fe0.2 Co0.2 Mo0.2 )B mainly results from reflection.